2013
DOI: 10.1002/iub.1138
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial energetic metabolism—some general principles

Abstract: Summary: In nonphotosynthetic organisms, mitochondria are the power plant of the cell, emphasizing their great potentiality for adenosine triphosphate (ATP) synthesis from the redox span between nutrients and oxygen. Also of great importance is their role in the maintenance of the cell redox balance. Even though crystallographic structures of respiratory complexes, ATP synthase, and ATP/adenosine diphosphate (ADP) carrier are now quite well known, the coupling between ATP synthesis and cell redox state remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 60 publications
0
29
0
1
Order By: Relevance
“…The enzyme activity of MRC proteins, which is essential for maintenance of the mitochondrial membrane potential (ΔΨm), is critical for ATP synthesis. Loss of the ΔΨm leads to a reduction in energy production, an increase in the permeability of the mitochondrial membrane, and the release of apoptotic factors such as cytochrome c , apoptosis‐inducing factor, and procaspases from the mitochondria into the cytoplasm …”
Section: Mitochondrial Activity In Oamentioning
confidence: 99%
“…The enzyme activity of MRC proteins, which is essential for maintenance of the mitochondrial membrane potential (ΔΨm), is critical for ATP synthesis. Loss of the ΔΨm leads to a reduction in energy production, an increase in the permeability of the mitochondrial membrane, and the release of apoptotic factors such as cytochrome c , apoptosis‐inducing factor, and procaspases from the mitochondria into the cytoplasm …”
Section: Mitochondrial Activity In Oamentioning
confidence: 99%
“…More importantly, although there is a direct stoichiometry between the oxidation of a substrate molecule and the production of NADHCH C and FADH 2 , NADHCH C can be reoxidised in reactions other than Complex I of the ETC and the proton motive force generated by the ETC can be dissipated by processes other than ATP synthesis (e.g. counter-ion transport and uncoupling protein activity) (Mazat et al 2013). The concepts of efficiency and plasticity in the coupling of substrate oxidation to energy conservation (ATP synthesis) have been expanded on in several authoritative review articles (Harper et al 2008, Mazat et al 2013.…”
Section: Fuel For Energy Productionmentioning
confidence: 99%
“…counter-ion transport and uncoupling protein activity) (Mazat et al 2013). The concepts of efficiency and plasticity in the coupling of substrate oxidation to energy conservation (ATP synthesis) have been expanded on in several authoritative review articles (Harper et al 2008, Mazat et al 2013. These review articles have highlighted the presence of a significant and variable basal proton leak in mitochondria (20-25%) of most tissues and reported that in perfused rat muscle systems futile proton cycling may contribute as much as 50% to the respiration rate (Rolfe & Brand 1996), although other methodologies have suggested that this could be as little as 10% (Marcinek et al 2004, Conley et al 2007.…”
Section: Fuel For Energy Productionmentioning
confidence: 99%
“…However, despite detailed crystallographic information, the precise mechanisms involved in this coupling remain unclear (Mazat et al, 2013). The unusual arrangement in terms of the biochemical synthesis being indirectly linked to the generation of potential and proton movement makes the system appear inexact and thereby to violate chemical principles (Wilson and Forman, 1982).…”
Section: Oxidative Phosphorylationmentioning
confidence: 98%
“…This gives a total of 10 potential protons pumped per NADH fed into the electron transport chain. The chemiosmotic mechanism provides a mechanism for connecting the energy derived from the flow of electrons down the respiratory electron transport chain to ATP synthase (or as it is sometimes referred to, complex V) (Mazat et al, 2013).…”
Section: Oxidative Phosphorylationmentioning
confidence: 99%